2010
DOI: 10.4061/2010/475260
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Growth and Osteogenic Differentiation of Mesenchymal Stem Cells by the Zinc-Added Sol-Gel Bioactive Glass Granules

Abstract: Responses of mesenchymal stem cells (MSCs) cultured with zinc-added (2 and 5%) bioactive glass granules were evaluated in terms of cell growth and osteogenic differentiation. MSCs were cultured with different quantities (3, 10 and 30) of glass granules for up to 21 days in the osteogenic medium. Cell growth was stimulated by a small quantity of glasses, particularly those that contained zinc. Osteogenic differentiation, as assessed by alkaline phosphatase activity (ALP) activity, was significantly enhanced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 23 publications
5
65
0
Order By: Relevance
“…32,33 The medium was replaced three times per week, and the cells were passaged at subconfluency. A 100 lL aliquot of the cells prepared at a density of 1 Â 10 5 /mL was plated in each well of 96-well plates.…”
Section: Cell Lines and Culturementioning
confidence: 99%
“…32,33 The medium was replaced three times per week, and the cells were passaged at subconfluency. A 100 lL aliquot of the cells prepared at a density of 1 Â 10 5 /mL was plated in each well of 96-well plates.…”
Section: Cell Lines and Culturementioning
confidence: 99%
“…The simultaneously incorporation of multi-walled carbon nanotubes (MWCNTs) and HA nanoparticles in PLLA nanofibers selectively increased adhesion of osteoblast cells and decreased the adhesion of osteoblast competitive cell lines, which was a valuable feature for GBR application [17]. The small trace amount of Mg [46,47], Si [48][49][50], and Zn ions [51,52] integrated in nanofibrous scaffolds have been proved to accelerate cell adhesion and proliferation by delivering the mitogenic stimuli and enhancing channel sensitivity. In addition, chemical signal molecules in the form of growth and differentiation factors [53,54] or plasmid DNA [55,56] incorporated in the nanofibers in a spatially defined manner could achieve corresponding bioactivity in promoting specific differentiation to orchestrate the growth of new tissue.…”
Section: Biological Events Occuring On the Biosis-abiosis Interface: mentioning
confidence: 99%
“…The apparent porosity of nanofibers was considered to favor efficient mass transportation of nutrients, oxygen, and waste products [48]. Recent studies have indicated a powerful role of the nanotopographic cues from nanofibers in regulating the osteogenic behavior of stem cells [51,52].…”
Section: Biological Events Occuring On the Biosis-abiosismentioning
confidence: 99%
“…A lot of work has been done to incorporate trace elements (e.g. silicon [121,122], zinc [123][124][125][126], strontium [122,127,128]) into synthetic bioceramics and improved biological performance was observed both in vitro and in vivo (e.g. silicon [49,121,129], zinc [39,[123][124][125][130][131][132][133][134][135][136][137][138][139][140], strontium [141,122,127,128,131,140,[142][143][144][145][146][147][148][149][150][151][152][153] and fluoride [64,65,67,…”
Section: Improve the Biological Performance Of Calcium Phosphates Witmentioning
confidence: 99%
“…Furthermore, some researchers showed that zinc could induce osteogenic differentiation of mesenchymal stem cells (i.e. bone marrow stromal cells) [124,125]. These facts indicated a possible role of zinc in ectopic bone formation (osteoinduction).…”
Section: Introductionmentioning
confidence: 99%